PENGARUH KEPATUHAN MENGIKUTI PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) TERHADAP KADAR HbA1C PADA PASIEN DIABETES MELLITUS DENGAN DISLIPIDEMIA - asri wido mukti (Yayasan Pendidikan Medika Indonesia, 2020)
Chronic Disease Management Program (PROLANIS) is a system of health and proactive services implemented by participants, Health Facilities and BPJS kesehatan in the context of health care for BPJS Kesehatan related participants to obtain optimal quality of life. Diabetes mellitus (DM) is a chronic disease that is the target of this program. Individuals with DM are usually with dyslipidemia. Dyslipidemia in diabetes increases the risk of cardiovascular disease. Objective: The purpose of this study is to analyze participating in prolanis activities on HbA1C levels in diabetes mellitus patients and to analyze the relationship of HbA1C with lipid risk. Method : This research is an analytic study using a retrospective cohort design. Patient data is secondary data from medical records (P-Care) of DM patients in primary care Klinik Pratama Sartika 59 Surabaya from January to May 2019. The research subjects involved 22 people who were active participants and had HbA1C data in May 2019. Results: The mean HbA1C value in patients who routinely followed the prolanis program (7.15 ± 1.51%) was more controlled than the mean HBA1C in patients who did not routinely participate in prolanis activities (7.95 ± 2.26%). The number of samples caused by differences in the value of HbA1C is not preferred in group 1 and group 2 with p = 0.389 (p> 0.05; CI = 95%). The trial by using the Pearson test between lipid profile with HbA1C obtained results that showed only significant parameters of TG lipids with HbA1C (p = 0.035). Conclusion: The number of samples caused by differences in the value of HbA1C is not preferred in group 1 and group 2 with p = 0.389 (p> 0.05; CI = 95%). Lipid parameters that have significant opposition to HbA1C are only TG lipid parameters. Keywords: Diabetes Mellitus, Dyslipidemia, HbA1C, Prolanis, Lipid Profile